Mechanical Properties of Boron and Kevlar-49 Reinforced Thermosetting Composites and Economic Implications - Kai, Kin Herbert Yeung; Rao, Kamineni Pitcheswara (Taylor's University, 2014)
A wider adoption of emerging thermosetting composite materials using Boron and Kevlar-49 fibres will be facilitated by establishing their mechanical properties and production costs. This study aims to characterise these reinforced composites on the basis of performance and economic considerations that can be readily used by manufacturers and designers. Composites with polyimide and polyester thermosetting plastics were prepared and tested in tension, compression and bending. The results are compared with those predicted by several micromechanics models and their limitations have been identified. The developed composites are ranked on a cost-performance basis that can be used for different applications.